Designing Android-Based Online Sales Applications to Increase Sales and Marketing - M Farhaan; D A Prasmanto; A Sumardi; S K Rahayu; Theresia Valentina Lumban Gaol (Peneliti.net, 2021)
The Cireng Manis (CiMan) design aims to increase the profitability of Cireng Manis fruit flavour sales by expanding the marketing strategy using android-based online. Therefore, it can be accessed by many people. The method used in making this application is the Waterfall System Development Life Cycle (SDLC) method. This application is based on Android using Java programming language and combines it with node JS as a database intermediary. This application makes our sales higher than usual because people more easily know our sales through social media. Other than that, it also makes it easier for customers to make purchases because they already use online transactions. Also, Cireng is also liked by almost all ages. Seeing these advantages, we will develop our application further to make it easier for everyone to use it to gain more benefits.